2021
DOI: 10.52082/jssm.2021.77
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Activity and Counselling Interventions on Health Outcomes among Working Women in Shanghai

Abstract: Working women in Shanghai are a high-risk group of suffering work stress and burnout. Women have been found to be affected by work-family conflicts, which results in lower health-related quality of life (HRQoL), higher job stress, and burnout. This study evaluated the potential physical activity and counselling intervention effects on health outcomes of working women in Shanghai. Participants were randomly recruited from eight communities of Shanghai using the stratified cluster sampling method. A total of 121… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…23 Contrary to this study's results, a study in China suggested that improving social relationships could be accomplished more effectively with group-based physical activity and counseling interventions. 4 likewise, another study revealed the existence of positive correlations between the physical, psychological, social, and Environmental domains of quality of life among the working-age population. 24 Moreover, the findings of this study suggest that physical activity adherence aims to improve women's health-related quality of life to cope with stress from home and work and prevent noncommunicable diseases (NCDs).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…23 Contrary to this study's results, a study in China suggested that improving social relationships could be accomplished more effectively with group-based physical activity and counseling interventions. 4 likewise, another study revealed the existence of positive correlations between the physical, psychological, social, and Environmental domains of quality of life among the working-age population. 24 Moreover, the findings of this study suggest that physical activity adherence aims to improve women's health-related quality of life to cope with stress from home and work and prevent noncommunicable diseases (NCDs).…”
Section: Discussionmentioning
confidence: 91%
“…2 Furthermore, a robust empirically based study among Chinese working women revealed that physical activity intervention could reduce stress and burnout and enhance health-related quality of life. 4 Findings demonstrated significant differences between the two groups related to their quality of life, suggesting that active mothers are more likely to have better physical and psychological domains and overall quality of life. This is consistent with the majority of intervention studies that are effective in improving health-related outcomes for working women.…”
Section: Dovepressmentioning
confidence: 91%
See 2 more Smart Citations
“…People will be more excited when doing sports with friends, trainers or family supported by a comfortable atmosphere so that exercise performance will increase. A Physical activity and counseling intervention delivered either in a group or individual format could reduce stress and burnout, and improve HRQoL of working [12]. It is related to the low hardy personality group, which means that they have less adaptation to the demands of the sports environment [13].…”
Section: Introductionmentioning
confidence: 99%